Effects of the Brand of Electrical Generator on the Concentration of Heavy Metals in Soil and Plants - Shakar Jamal Aweez; Zhian Rashid Salih; Lubna ahmad abdulkarim; Aveen Muhsin Asaad (Zanco Journal of Pure and Applied Sciences, 2023)
There are serious health and environmental problems caused by the use of diesel generators for backup power at many locations. For this purpose, ten different locations (Baharykon S1, Azadi 1 S2, Azadi 2 S3, Nasejan S4, Kuran S5, Nawroz S6, Kurdistan S7,92 Zanko S8, Nargz S9, and Nishtiman S10) were selected. Three different brands of electrical generators were used (B1 Cater piller, B2 Cummins, and B3 Locally manufactured aggregates). The heavy metals (As, Cd, Cr, Cu, Zn, Pb, and Hg) were determined from both soil and plants. For soil pollution assessment indices were applied contamination factor (CF), degree of contamination (Cdeg), Ecological Risk Factor, Potential Ecological Risk Indices, and biological accumulation factor. Results showed that the highest values of (5.368, 232.873, 3.023, 4.205, 1.697, 4.101,0.178) were recorded in (B2S2, B3S5, B2S9, B3S5, B3S1, B2S9) while for the degree of contamination was (249.199) were recorded in (B3S5). According to contamination factor their indications of low contamination (B2S9) moderate contamination factor for (B2S9) considerable contamination factor for (B2S2, B2S9, B3S5, B3S1), with high degree of contamination in (B3S5). The ecological risk factor and RI with the highest values were (53.682, 6986.193, 6.046, 21.027, 1.697, 20.507,13.936) and RI was (7081.261), which were recorded in (B1S2, B3S5, B2S9, B3S5, B3S1, B2S7) and (B3S5), respectively. The ecological risk factor and potential ecological risk indices showed that (B2S9, B3S5, B3S1, B2S7) low potential ecological risk, (B1S2) moderate potential ecological risk, (B3S5) very high ecological risk. The biological accumulation coefficient factor of two different plants (Eucalyptus amygdalina Labill, (Plant1), and Dodonaea viscosa Jacq (Plant2 ) are (8.433, 15.358, 23.311, 42.236, 52.626, 48.094, 0.190) which were recorded in (B3S8P1, B2S7P1,S3S5P2, B2S9P2, B2S7P2, B3S8P1,B3S4P1.The aim of this study is to assess the effect of the brand electrical generator on concentration heavy metal in soil and dust soil and plant heavy metal levels in Erbil city